Aminoferrocene‐Based Anticancer Prodrugs Labelled with Cyanine Dyes for in vivo Imaging. Issue 48 (14th December 2021) - Gizem Özkan, Hülya; Toms, Johannes; Maschauer, Simone; Prante, Olaf; Mokhir, Andriy
Abstract: N‐alkylaminoferrocene‐based (NAAF) prodrugs are activated in the presence of reactive oxygen species (ROS), based on which these prodrugs target cancer cells (high ROS) and do not affect normal cells (low ROS). To gain some insights into their mode of action in vivo, we have investigated the biodistribution of 18 F‐labelled NAAF prodrugs in tumor‐bearing mice by positron emission tomography (PET). Due to the short half‐life of 18 F, the experimental time frame was restricted to 60 min. To extend the observation window, a more stable marker is required. In this paper, we report on conjugates of NAAF prodrugs with two cyanine dyes Cy5 and Cy7 including details of their synthesis, characterization and basic properties in cell free settings and their cellular uptake in representative human cancer cells. Finally, the Cy5 conjugate was subjected to in vivo fluorescence imaging studies to determine the prodrug biodistribution over 24 h. Abstract : N‐alkylaminoferrocene‐based anticancer NAAF prodrugs labelled with Cy5 dye were prepared and characterized. We demonstrated that these conjugates behave similarly to unlabeled NAAF prodrugs: accumulation in mitochondria, activation in cancer, but not in normal cells. Furthermore, we confirmed that these conjugates are suitable for studies of distribution and accumulation of NAAF prodrugs in live cells as well as in organs and tumors in vivo .